2016
DOI: 10.1111/1744-7917.12339
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of miRNAs and transcriptomes inAedes albopictusmidgut reveals the differential expression profiles of immune-related genes during dengue virus serotype-2 infection

Abstract: Mosquito microRNAs (miRNAs) are involved in host-virus interaction, and have been reported to be altered by dengue virus (DENV) infection in Aedes albopictus (Diptera: Culicidae). However, little is known about the molecular mechanisms of Aedes albopictus midgut-the first organ to interact with DENV-involved in its resistance to DENV. Here we used high-throughput sequencing to characterize miRNA and messenger RNA (mRNA) expression patterns in Aedes albopictus midgut in response to dengue virus serotype 2. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
(61 reference statements)
1
19
1
Order By: Relevance
“…For example, miR-87 is downregulated in A. albopictus mosquitoes infected with DENV-2; the target genes of this miRNA include Pelle, Toll1A receptor, class A scavenger receptor with serine protease domain (SCRASP1) and galectin. However, miR-34-5 p was upregulated, and its target is Rel1 [8]. In agreement with this hypothesis, the inhibition or overexpression of miR-927 resulted in changes in the expression of Cecropin A, Cecropin G and Defensin D -all antimicrobial peptides associated with the Toll pathway response.…”
Section: Mir-927 Modifies the Expression Of Effector Genes Implicatedsupporting
confidence: 63%
See 1 more Smart Citation
“…For example, miR-87 is downregulated in A. albopictus mosquitoes infected with DENV-2; the target genes of this miRNA include Pelle, Toll1A receptor, class A scavenger receptor with serine protease domain (SCRASP1) and galectin. However, miR-34-5 p was upregulated, and its target is Rel1 [8]. In agreement with this hypothesis, the inhibition or overexpression of miR-927 resulted in changes in the expression of Cecropin A, Cecropin G and Defensin D -all antimicrobial peptides associated with the Toll pathway response.…”
Section: Mir-927 Modifies the Expression Of Effector Genes Implicatedsupporting
confidence: 63%
“…They have also been proposed as biomarkers of infection, adjuvants for antiviral treatment and as a method to improve vaccines [1]. miRNAs have been detected in mosquito vectors such as Culex quinquefasciatus [3], Aedes aegypti [3][4][5][6] and Aedes albopictus [7][8][9]. They are part of the antiviral innate immune response in addition to short interfering RNAs (siRNAs) and PIWI-interacting RNAs (piRNAs) [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In another study from the same group with Ae . albopictus and DENV2 infection specifically in the midgut tissue, three miRNAs (miR-2941, miR-989, miR-2943) were differentially expressed [ 29 ], the first two also with change in abundance upon ZIKV infection in this study. Furthermore, miR-989 was found to be depleted in Culex quinquefasciatus mosquitoes by 2.8-fold when infected with WNV [ 30 ]; although this miRNA was enriched by about 1.8-fold at 2 and 14 dpi with ZIKV in the present study.…”
Section: Resultsmentioning
confidence: 73%
“…Liu et al . reported an integrated analysis of micro RNAs (miRNAs) and transcriptomes in the midgut of Aedes albopictus (Liu et al ., ). They showed differential expression profiles of immune‐related genes during infection by dengue virus serotype‐2.…”
mentioning
confidence: 97%
“…Transcriptome data are powerful tools for direct identification of genes and analysis of global gene expression profiles. Liu et al reported an integrated analysis of micro RNAs (miRNAs) and transcriptomes in the midgut of Aedes albopictus (Liu et al, 2016a). They showed differential expression profiles of immune-related genes during infection by dengue virus serotype-2.…”
mentioning
confidence: 99%